Structure and composition of tree community in the upstream area of Batang Mahat Watershed, Lima Puluh Kota District, West Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ekawaty E, Yonariza, Ekaputra EG, Arbain A. 2021. Structure and composition of tree community in the upstream area of Batang Mahat Watershed, Lima Puluh Kota District, West Sumatra, Indonesia. Biodiversitas 23: 687-696. Land-use change at the upstream area of Batang Mahat Watershed is assumed to cause flood during the rainy season and is related to vegetation community which has been heavily exploited. Information regarding the current vegetation condition in this area has never been studied; therefore, this study aims to investigate the structure and composition of the tree community in the upstream area of Batang Mahat at Jorong Kubu Baru Nagari, Baruh Gunung, Bukit Barisan District. Furthermore, sampling was implemented using three 20x50 m belt-transects with 10 m intervals between each sample. The results showed 1) 116 identified and three unidentified tree samples belonging to 40 families; 2) The trees with the highest important value index (IVI) in transect 1 were Rhodoleia championii (63.339%) and Calophylum soulatteri (23.697%), in transect 2 Voacanga foetida (48.568%) and Schima wallichii (32.756%), and in transect 3 Schima wallichii (42.964%) and Voacanga foetida (40.713%); 3) The saplings with the highest IVI in transect 1 were Timonius sp. (33.111%) and Alstonia sp. (21.345%), in transect 2 Hancea pengangensis (24.551%) and Sterculia sp. (21.199%), as well as transect 3 Voacanga foetida (42.862%), and Macaranga lowii (30.844%); 4) Both vegetation categories have considerably high diversity (H’ tree 3.13-3.2, H’ saplings 3.04-3.36), and were moderately distributed across studied transects (E1 = 2.025, E2 = 2.089, E3 = 2.016). From the results, it can be concluded that the forest in the upstream area of the Batang Mahat watershed, which was located in Jorong Kubu Baru, Nagari Baruh Gunung, was still in the good category.